Degradation of methylene blue by three-dimensional heterogeneous electro-Fenton system with CuFeKao particle electrode - CHEN Yue; PENG Xueer; ZHOU Chenyang; LI Jing; MENG Xinyi; GAO Lili (Gongye shui chuli, 2025)
CuFe2O4/Fe2O3/Kaolin(CuFeKao) catalytic particle electrode was synthesized by sol-gel method and used in three-dimensional heterogeneous electro-Fenton system to degrade Methylene blue(MB). XRD results showed that CuFeKao was a composite material composed of CuFe2O4, Fe2O3 and Kaolin. Through comparative experiments, it was found that three-dimensional electrochemical interactions could increase the yield of H2O2, and heterogeneous electro-Fenton systems could catalyze the in-situ conversion of H2O2 to ·OH. Compared with 3D systems using CuFe2O4/Fe2O3 or Kaolin as particle electrode and 2D systems, the 3D/EF/CuFeKao system exhibited the highest ·OH yield and the best MB degradation effect. The degradation conditions of the 3D/EF/CuFeKao system were optimized by single factor experiments. Under the optimized conditions, the removal rates of MB and TOC could reach 99.81% and 58.13% respectively after 60 minutes of reaction. The quenching of free radicals confirmed that the system contained two reactive oxygen species, ·OH and O2·-, whose relative proportions could be regulated by solution pH. Mechanism analysis showed that the main mechanism of MB degradation in the 3D/EF/CuFeKao system is the heterogeneous electro-Fenton reaction occurring on the surface of the CuFeKao particle electrode.